Assessment of Water Quality in and Around Jamkhandi City, Bagalkot District, Karnataka State, India. (Global Journal of Science Frontier Research, 2013)
The assessment of water quality and suitability for drinking and domestic (cooking) purposes was carried out from Jamkhandi city of Bagalkot District. The Bore water (Ground water), Surface water (Open well water) and Municipal water were assessed by examining various physico-chemical parameters such as pH, EC, TDS, TA, TH, DO, COD, BOD, Calcium, Magnesium, Chloride, Sulphate , Sodium and Trace element concentration like Iron, Manganese Cobalt and Copper called dissolved metals have been analyzed. The analyzed results were compared with WHO and ISI drinking water standards. On the basis of pH, EC and Hardness out of 62 Bore wells, 08 Open wells and 09 Municipal water samples, 57 Bore wells, 06 Open wells and all 09 municipal water samples were within the permissible limit and useful (safe) for drinking and cooking purposes.
Keywords: jamkhandi city; ground water; open wells; municipal water; physico-chemical parameters